Выравнивание дифтонгов в западномерсийском диалекте древнеанглийского языка - Армалите, О. (Kalbotyra, 1979)
Smoothing, a prominent feature of the West Mercian dialect, consisted in monophthongization of OE diphthongs /ēa ēo īo/ before dorsal consonants spelt c, ʒ, h, and diphthongs /ěa ěo io/ before clusters ht, lc, lʒ, lh, rc, rʒ, rh and before h. Phonetic causes of smoothing are to be sought in certain peculiarities of the OE consonant system. The split of PE /k/ and /ʒ/ into velar /k’/ /ʒ/ and palatal /k’/ /ʒʒ’/ in the 7th century was soon followed by assibilation of /k’/ /ʒʒ’/ into /tš/ and /dž/. After the assibilation which must have occurred in the 7th-8th centuries (at least in the Anglian dialects), the position of the tongue ceased to be a relevant feature of the velar /k/ /ʒ/. They could now develop new allophones depending upon the nature of the preceding vowel. After front vowels and diphthongs /k/ developed a palatal allophone [k’] which absorbed the second, velar component of the preceding diphthong. Voiced and voiceless fricatives retained complementary distribution of their velar and palatal allophones even after i-Umlaut. Diphthongs before [γ’] and [χ’] lost their second component. Smoothing which belongs to the period after i-Umlaut (the 7th-8th centuries) reduced the distribution of diphthongs in West Mercian considerably.